Insider Trades and Private Information: The Special Case of Delayed-Disclosure Trades - Cheng, Shijun; Nagar, Venky; Rajan, Madhav V. (Review of Financial Studies, 2007)
In certain circumstances, insider trades such as private transactions between executives and their firms could be disclosed after the end of the firm's fiscal year, on a Form-5 filing. We find that insider sales disclosed in such a delayed manner for large firms are predictive of negative future returns (−6 to −8 percent), as well as lower future annual earnings relative to analyst forecasts. These results stand in contrast to existing findings on the uninformativeness of quickly disclosed open-market insider sales. The Sarbanes-Oxley Act curtailed the use of Form 5 under the presumption that managers used this vehicle opportunistically. Our systematic evidence supports this presumption.